Longitudinal comparison of Streptococcus mutans-induced aggravation of non-alcoholic steatohepatitis in mice. Issue 1 (1st January 2018) - Naka, Shuhei; Wato, Kaoruko; Hatakeyama, Rina; Okawa, Rena; Nomura, Ryota; Nakano, Kazuhiko
ABSTRACT: Background : We previously reported that intravenous administration of Streptococcus mutans strain TW871 caused typical non-alcoholic steatohepatitis (NASH)-like findings in a high-fat diet (HFD) mouse model at 16 weeks after initiating the experiment. Objective : The purpose of the present study was to analyse mice administered S. mutans TW871 fed a HFD for various periods of time. Methods : First, 6-week-old C57BL/6J mice were fed an HFD for 4 weeks, then TW871 (1 × 10 7 CFU) or phosphate-buffered saline (PBS) were intravenously administered. Mice were euthanized 12, 16, 20, and 48 weeks after starting the experiment, and conventional clinical and histopathological evaluations were performed. Results : Typical NASH-like findings were not identified in the mice at 12 weeks, while they were observed in the TW871 group at 16 weeks, and the severity of NASH symptoms were increased at 20 weeks. Furthermore, signs of severe NASH were also observed at 48 weeks. In contrast, in the PBS-administered group, the NASH findings were identified only at 48 weeks and no typical NASH features were observed at 12, 16, or 20 weeks. Conclusion : These results suggest that intravenous administration of a specific S. mutans strain aggravates NASH in a time-dependent manner in the mice in contrast to mice without S. mutans exposure.